2007
DOI: 10.3390/medicina44010003
|View full text |Cite
|
Sign up to set email alerts
|

Natural clearance of hepatitis C virus in hemophilia patients

Abstract: Summary. Objective. The objective of this study was to investigate the prevalence of HCV (hepatitis C virus) infection in hemophilia patients in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 23 publications
1
11
1
3
Order By: Relevance
“…In our patients with positive anti-HCV, the spontaneous elimination rate of HCV RNA (29.6%) was similar to that found in other publications (2, 26, 27). The predominant HCV genotype was 1 (65.1%), which is the most common genotype in the general Polish population (28).…”
Section: Discussionsupporting
confidence: 91%
“…In our patients with positive anti-HCV, the spontaneous elimination rate of HCV RNA (29.6%) was similar to that found in other publications (2, 26, 27). The predominant HCV genotype was 1 (65.1%), which is the most common genotype in the general Polish population (28).…”
Section: Discussionsupporting
confidence: 91%
“…In particular, many studies define HCV-infected infants through the persistence of anti-HCV after 18 months of age [8,20,29] (by which point all passively transferred maternal anti-HCV has generally been lost). Spontaneous HCV clearance can occur in 25%-30% of children [29,48]. In our study, we cannot exclude the possibility that we underestimated the rate of MTCT of HCV by missing subjects who spontaneously cleared the HCV virus before the first sample was obtained at 6-12 weeks of age.…”
Section: Discussioncontrasting
confidence: 39%
“…The presence of transient viremia should be regarded as a consequence of spontaneous viral clearance after MTCT [31,36,46]. Most studies have not been able to establish a clear association between HCV genotype and MTCT [26,47,48]. One study suggested that genotypes 1b and 3a are associated with MTCT of HCV, although they were also more prevalent in HCV/HIV-coinfected mothers [38].…”
Section: Discussionmentioning
confidence: 99%
“…Our data support the suggestion that acquiring HCV infection at younger ages is associated with a greater level of clearance of the virus than in adults. 10,28 …”
Section: Discussionmentioning
confidence: 99%